Carpooling in transport in today's ICT – based economy - Wiączek, Paulina; Sitak, Iryna; Novák Sedláčková, Alena; Novák, Andrej; Bugaj, Martin (University of Žilina, 2025)
The purpose of this research was, among other things, to show that the carpooling model can be regarded as a manifestation of collective intelligence and a response to the crisis of sustainability in today's ICT-based economy, which makes carpooling services a cheaper alternative to transportation services provided by other modes of transport: train and bus. The main research problem is contained in the question: How do collective intelligence and the tenets of sustainability influence the popularity of carpooling and the lower cost of carpooling services, compared to those provided by other forms of transportation? The critical literature analysis method, the comparison method and the statistical method, among others: the Mann Whitney U test and the Kruskal Wallis ANOVA test, were used in implementation of the study.
Keywords: carpooling; collective intelligence; sustainability; technological innovation; travel model; transportation; transportation economics